‘It benefits patient care’: the value of practice-based IPE in healthcare curriculums - O’Leary, Noreen (BMC Med Educ, 2020)
BACKGROUND: Practice-based interprofessional education (IPE) is essential to prepare students for collaborative working. Pockets of practice-based IPE are integrated into healthcare curriculums in some regions. Yet practice-based IPE is not globally valued as a key element of healthcare curriculums. As students and clinical educators are key stakeholders, this study presents a case example of their experiences in a country where practice-based IPE is at an emergent stage. Their experiential knowledge generated important insights into how practice-based IPE is perceived. This learning can be applied, both locally and further afield, by those seeking to embed practice-based IPE in their placement curriculums. METHODS: A qualitative case study was conducted at a school of allied health and partner placement sites in Ireland. Data collection comprised two participant observations, 13 interviews and 12 document analyses. Inductive thematic analysis and deductive framework analysis, underpinned by activity theory and Hofstede’s cultural dimensions, informed data analysis and interpretations. RESULTS: Participants are grappling to establish the value of practice-based IPE, illustrated in three themes: clarifying the concept of practice-based IPE, mapping IPE activities and diversifying interprofessionalism. First, ambiguous conceptualisation of why and how to implement practice-based IPE was identified. Highlighting how practice-based IPE improved patient care and safety created a clear rationale for implementation. It was also helpful to demonstrate how adaptations to existing practice education models, rather than entirely new models, could achieve high-quality practice-based IPE. Second, the positioning of practice-base IPE in the placement curriculum was unclear. Overt mapping of practice-based IPE activities onto learning outcomes within assessment tools enhanced its value within practice education. Third, varying levels of professional engagement were noted, perpetuating stereotypes. Creating diverse educator networks and embedding practice-based IPE in organisational strategy may incentivise engagement across a greater range of professions. CONCLUSIONS: Implementing these recommendations could enhance the value of practice-based IPE and optimise student preparation for collaborative working. Practice-based IPE remains a complex model and the trajectory of embedding in healthcare curriculums will differ globally. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12909-020-02356-2.